Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1063/1.481369
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CH3OH2+ and H3O+-centered cluster isomers from fragment-dependent vibrational predissociation spectra of H+(CH3OH)4H2O

Abstract: Cluster isomers of H ϩ ͑CH 3 OH͒ 4 H 2 O have been identified by vibrational predissociation spectroscopy in combination with mass-selected detection of photofragments. Ab initio calculations indicate that the cluster ion can exist in either CH 3 OH 2 ϩ ͑CH 3 OH͒ 3 H 2 O or H 3 O ϩ ͑CH 3 OH͒ 4 isomeric forms. They can dissociate via a methanol loss or water loss channel, depending on the structure of the isomers. While water loss is the dominant channel of the dissociation, the methanol loss channel is readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…The isomers that are most likely to be responsible for the experimental spectra are WM4I and WM4III (cf. Figure ), as assigned previously is not found in the experimental spectra.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…The isomers that are most likely to be responsible for the experimental spectra are WM4I and WM4III (cf. Figure ), as assigned previously is not found in the experimental spectra.…”
Section: Methodssupporting
confidence: 77%
“…Previously, we reported results of our attempts to observe these intriguing HB rearrangements using vibrational predissociation spectroscopy in combination with density functional theory calculations. Both H 3 O + -centered and CH 3 OH 2 + -centered treelike isomers have been experimentally identified for H + (CH 3 OH) 4 (H 2 O); however, the thorough dynamical mechanism by which these isomers are interconverted is still not known.…”
Section: Introductionmentioning
confidence: 99%
“…Sıvı ve katı fazda bu nedenle 2 boyutlu zig-zag zincir oluşturur ve zincirler van der Waals kuvvetleri ile bir arada tutunurlar [5]. Nötral ve protonlanmış su ve metanol kümeleri bir çok grup tarafından hem deneysel hem de teorik olarak çalışılmıştır [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionunclassified
“…Protonated (methanol) n –(water) m mixed clusters (H + M n W m ) are one of fundamental model systems of protonated binary mixed clusters of protic molecules. Many spectroscopic and mass spectrometric studies combined with quantum chemical calculations have been performed on H + M n W m to understand the size dependence of their proton solvation motifs. For the small sizes ( n + m ≤ ∼5), the exhaustive infrared (IR) studies have elucidated the competition between the two ion cores (protonated sites), H 3 O + and MeOH 2 + , with the change of the ratio of the two components. ,,,, The H-bonded network structure changes with the switching of the ion core type. In addition, it has also been demonstrated that the two different dissociation channels (water-loss and methanol-loss) compete with each other and they correlate to the ion core type.…”
Section: Introductionmentioning
confidence: 99%
“…39−60 For the small sizes (n + m ≤ ∼5), the exhaustive infrared (IR) studies have elucidated the competition between the two ion cores (protonated sites), H 3 O + and MeOH 2 + , with the change of the ratio of the two components. 52,53,55,59,60 The H-bonded network structure changes with the switching of the ion core type. In addition, it has also been demonstrated that the two different dissociation channels (water-loss and methanol-loss) compete with each other and they correlate to the ion core type.…”
Section: Introductionmentioning
confidence: 99%